Adaptive Tomotherapy for locally advanced unresectable pancreatic neuroendocrine tumor: Case report and literature review - Tu, Kuan-Yi; Huang, Yen-Shuo; Lau, Juntiong; Lee, Hsin-Hua (Frontiers in Oncology, 2022)
Background: Pancreatic neuroendocrine tumor (NET) is rare and the majority presents late in their clinical course. Here we present a huge locally advanced pancreatic NET having Hi-Art helical Tomotherapy that resulted in a 68% reduction in target volume during adaptive image-guided radiotherapy (IGRT). Case summary: A 63-year-old man without any history of systemic disease developed voiding difficulty for several months. Associated symptoms included poor appetite, nausea, distended abdomen and body weight loss. Further magnetic resonance imaging showed a large multilobulated tumor in the left upper abdomen. Tumor biopsy revealed well-differentiated, grade 2, neuroendocrine tumor. Complete resection was unattainable. Therefore, Lanreotide was prescribed initially. However, tumor progression up to the greatest diameter of 18 cm was noted on computed tomography five months later. So he stopped Lanreotide and commenced on concurrent chemoradiotherapy (CCRT). With total dose of 70Gy in 35 fractions, we generated two adaptive treatment plans during the whole course. Laparoscopic subtotal pancreatectomy with spleen preservation was performed after neoadjuvant CCRT. It has been more than three years after IGRT, and he remains cancer free and reports no side effects during regular follow-ups. Conclusion: Tomotherapy caused tumor size reduction and hence facilitated surgical possibility for this originally unresectable pancreatic NET. Neoadjuvant IGRT incorporated with adaptive treatment planning enhanced delivery accuracy. In this case of pancreatic NET resistant to Lanreotide, inter-fractional tumor regression from 1910 cc to 605 cc (68%) was documented.